IMPLEMENTASI SISTEM E-LEARNING BERBASIS RESOURCE SHARING UNTUK PENGEMBANGAN SDM UMKM PADA UPT PLUT SULAWESI SELATAN - Dinda Putri Oetami; Mustari S. Lamada; Patang (UNM Journal of Technology and Vocational, 2022)
The purpose of this study is to develop an e-learning system based on resource sharing for the development of MSME human resources at the South Sulawesi PLUT UPT, where the South Sulawesi PLUT human resources previously had a website, and MSMEs who have understood the use of digital applications where the final result will be a further analysis process. for implementation. This type of research is Research and Development (R&D) and the output in particular is in the form of elearning learning products based on LMS (Learning Management System) which are made by themselves using CodeIgniter Framework, Mysql Database, and Programming Language using PHP. The implementation test uses the implementation analysis method using a descriptive percentage technique with variables of validity, practicality, effectiveness, and user responses being assessed by distributing questionnaire-based implementation test results. The results showed the validity showed a score of 4.83 with the conclusion that the system was valid for implementation, practical with a score of 4.62 was very practical to use, effectiveness with a score of 4.85 was very effectively implemented, and the final score of the responses of 30 MSMEs as users stated 93, 75% said it was very effective inthe learning process and was satisfied with the developed application